New insights on the molecular phylogenetic relationships of paradoxical frogs of the genus Pseudis with emphasis on the systematics of P. platensis - Caballero-Gini, Andrea; Brusquetti, Francisco; Bueno-Villafane, Diego [UNESP]; Quinteros-Munoz, Oliver; Jairam, Rawien; Rodrigues, Miguel Trefaut; Haddad, Celio F. B [UNESP]; Fernandez Rios, Danilo; Baldo, Diego (Oxford University Press (OUP), 2024)
Paradoxical frogs are exclusively aquatic anurans distributed across much of South America. They have been the subject of several phylogenetic studies, but the results of these studies are contradictory regarding the monophyly of PseudisWagler, 1830 and the validity of some species, including Pseudis platensisGallardo, 1961. Using two mitochondrial and three nuclear genes, together with a comprehensive sampling of Pseudis species and an extensive outgroup, we aimed to assess the monophyly of the genus and investigate the systematics of P. platensis. The results of distinct phylogenetic reconstruction analyses based on different optimality criteria recovered conflicting topologies regarding the clade containing Pseudis minutaGünther, 1858 and Pseudis cardosoiKwet, 2000. Therefore, we propose synonymizing Lysapsus Cope, 1862 with Pseudis to maintain taxonomic stability. Additionally, our results revealed previously unrecognized diversity within Pseudis paradoxa Linnaeus, 1758 and P. platensis. Both species comprised multiple well-supported clades in phylogenetic inferences using different approaches. Notably, P. platensis consisted of three clades, one of which included the topotype of the species. Conversely, the topotype of the subspecies P. paradoxa occidentalis, currently considered a synonym of P. platensis, was nested within one of the clades of P. paradoxa.
Keywords: Lysapsus; multilocus phylogeny; Pseudis paradoxa occidentalis; unrecognized diversity